2016
DOI: 10.1007/s10157-016-1293-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic kidney disease on hospitalization, chronic dialysis, and mortality in Japanese men: a longitudinal analysis

Abstract: In Japanese men, although the risk of CVD death before dialysis initiation can never be ignored, CKD patients aged <60 years with a GFR of <30 mL/min/1.73 m are more likely to undergo dialysis prior to death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Several other studies examined the incidence of ESRD stratified by eGFR or albuminuria as well (Tonelli et al 2011;Coresh et al 2014;Wada et al 2014;Tanaka et al 2015). Nishikawa et al (2017) used data from one employer-based insurer, including health checkup and claims data, to investigate the risk of dialysis initiation among male workers in Japan. The incidence according to eGFR level in their study was not different from that found in the current study, except for the rate of the subjects with stage G3b CKD (12.5/1,000 by Nishikawa et al (2017) vs. 2.57/1,000 in the present study); the discrepancy might stem from differences in patient characteristics, such as sex, age, and employment status, as well as the observation periods (2006-2013 vs. 2012-2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies examined the incidence of ESRD stratified by eGFR or albuminuria as well (Tonelli et al 2011;Coresh et al 2014;Wada et al 2014;Tanaka et al 2015). Nishikawa et al (2017) used data from one employer-based insurer, including health checkup and claims data, to investigate the risk of dialysis initiation among male workers in Japan. The incidence according to eGFR level in their study was not different from that found in the current study, except for the rate of the subjects with stage G3b CKD (12.5/1,000 by Nishikawa et al (2017) vs. 2.57/1,000 in the present study); the discrepancy might stem from differences in patient characteristics, such as sex, age, and employment status, as well as the observation periods (2006-2013 vs. 2012-2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nishikawa et al (2017) used data from one employer-based insurer, including health checkup and claims data, to investigate the risk of dialysis initiation among male workers in Japan. The incidence according to eGFR level in their study was not different from that found in the current study, except for the rate of the subjects with stage G3b CKD (12.5/1,000 by Nishikawa et al (2017) vs. 2.57/1,000 in the present study); the discrepancy might stem from differences in patient characteristics, such as sex, age, and employment status, as well as the observation periods (2006-2013 vs. 2012-2017). Smaller sample size may also have caused larger chance errors and resulting discrepancies, especially in the stratified analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, all-cause hospitalization increased with CKD stage [ 16 ]. Meanwhile, Japanese medical checkup data have shown that a lower estimated glomerular filtration rate (eGFR) is associated with increased risk of all-cause hospitalization and CVD death [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical and dental fee receipts were sent monthly to the KSHIA by the hospitals that insured employees consulted, as shown in our previous study. 31 We followed all receipts from January 2010 to December 2013. Receipts were divided into the following four categories: medical inpatient, medical outpatient, dental inpatient, and dental outpatient.…”
Section: Follow-up and Endpointsmentioning
confidence: 99%